2016
DOI: 10.1007/s40258-016-0265-y
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Economic Evaluation Methodologies Between Resource-Limited and Resource-Rich Countries: A Case of Rotavirus Vaccines

Abstract: Although the quality of economic evaluations in LMICs was not as high as those from HICs, it is of an acceptable level given several limitations that exist in these settings. However, the results of this study may not reflect the fact that LMICs have developed a better research capacity in the domain of health economics, given that most of the studies were in theory led by researchers from HICs. Putting more effort into fostering the development of both research infrastructure and capacity building as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Findings in many studies have further indicated that the issues on availability and quality of data used in the economic evaluation as well as relevant research standards are significant in LMICs [ 5 , 6 , 8 ]. Although some data, such as treatment effect, is considered transferable across settings [ 9 ] (and therefore researchers may choose to borrow from other contexts), application of this approach to other types of inputs that are more context-specific (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Findings in many studies have further indicated that the issues on availability and quality of data used in the economic evaluation as well as relevant research standards are significant in LMICs [ 5 , 6 , 8 ]. Although some data, such as treatment effect, is considered transferable across settings [ 9 ] (and therefore researchers may choose to borrow from other contexts), application of this approach to other types of inputs that are more context-specific (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, those contemplating such implementation should consider not only the vaccine’s clinical effectiveness but also its cost-effectiveness, which is particularly important in LICs and LMICs. Nevertheless, economic evaluations of rotavirus vaccine are still limited in LICs and LMICs owing to lack of both local cost and clinical effectiveness data and the research capacity to conduct such evaluations [3, 10, 11]. Therefore, systematic reviews of published economic evaluations of rotavirus vaccine could be used as the evidence to guide decisions about vaccine policy.…”
mentioning
confidence: 99%
“…Many individual studies have been conducted across the world to assess the cost-effectiveness of rotavirus vaccines, and these individual evidences have been summarized in 2 systematic reviews [3, 11]. However, the systematic review by Thiboonboon et al [11] mainly focused on methodological differences between economic studies conducted in high-income countries (HIC) and in LMICs, whereas the systematic review by Kotirum et al [3] provided only qualitative evidence without distinguishing LICs and LMICs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We also carried out searches of the first 150 hits in Google and Google Scholar using BIA-specific search terms to identify any unpublished BIAs (Online Resource 1 of the ESM). We supplemented the database searches by conducting manual bibliographic searches from recent and relevant rotavirus vaccine review papers [ 14 , 15 , 29 , 33 35 ].…”
Section: Methodsmentioning
confidence: 99%